The benefits of banks' IT investments in times of trouble: evidence from loan loss accruals during the COVID-19 pandemic - Moritz Sefried; Jan Riepe (Journal of Business Economics, 2022)
Motivated by diverging results from the literature, we investigate whether investments in information technology (IT) help banks to assess their loan portfolio. More specifically, we focus on the consequences of accumulated expenses for data processing on banks' ability to estimate their loan loss accruals. We further test for differences when the banks' borrowers get hit by the economic trouble from the COVID-19 pandemic. Using a sample of US commercial banks before and during the COVID-19 pandemic, we find more precise estimates of loan loss accruals during these troublesome times in banks that accumulated higher data processing expenses. Surprisingly, we do not find significant differences in the precision of loan loss accruals by banks' IT investments during normal times. Our findings contribute to consolidate previously diverging results by showing that IT investments help banks following a structural break, such as the COVID-19 pandemic.
Keywords: G21; G32; M41; 650; Bank accounting; Loan loss provisions; IT investments; COVID-19 pandemic